Domestic violence and multi-agency risk assessment conferences (MARACs): a scoping review. Issue 6 (2nd December 2014) - Robbins, Rachel; McLaughlin, Hugh; Banks, Concetta; Bellamy, Claire; Thackray, Debbie
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to draw attention to the potential and limits of the Multi-Agency Risk Assessment Conferences (MARACs) in supporting adults with social care needs who also experience domestic violence. Design/methodology/approach – The paper reports on a scoping review as part of a wider research project entitled: to identify and assess the effectiveness of social care's contribution to the development of MARAC and the protection of adults facing domestic violence. Findings – An understanding of the workings of MARAC could support social care practice with high-risk victims of domestic violence. However, the conception of risk assessment and management central to the process also poses ethical dilemmas for practitioners. Practical implications – Social care is ideally placed to support, in an holistic manner, a group of vulnerable service-users with complex needs. However, the current climate of austerity could jeopardise this work. Originality/value – There is little in the professional and academic press on the MARAC process and particularly in relation to adults and older people. This paper alerts the practice community to the process, its historical development and characteristics and implications for practice.